Prevalence of post-traumatic stress disorder in the United States: a systematic literature review. (2nd December 2021) - Schein, Jeffrey; Houle, Christy; Urganus, Annette; Cloutier, Martin; Patterson-Lomba, Oscar; Wang, Yao; King, Sarah; Levinson, Will; Guérin, Annie; Lefebvre, Patrick; Davis, Lori L.
Abstract: Objective: This study synthesized evidence regarding the prevalence of post-traumatic stress disorder (PTSD) in the United States (US). Methods: A systematic literature review (SLR) identified recently published (2015–2019) observational studies of PTSD prevalence in the US via the MEDLINE, EMBASE, and PsycINFO databases. Eligible studies' most recent data were collected no earlier than 2013. Data elements extracted included study design, sample size, location, data source/year(s), study population(s), traumatic event type, prevalance estimates with corresponding look-back periods, and clinical metrics. Results: Data from 38 identified articles were categorized by population, diagnostic criteria, and lookback period. Among civilians, point prevalence ranged from 8.0% to 56.7%, 1-year prevalence from 2.3% to 9.1%, and lifetime prevalence from 3.4% to 26.9%. In military populations, point prevalence ranged from 1.2% to 87.5%, 1-year prevalence from 6.7% to 50.2%, and lifetime prevalence from 7.7% to 17.0%. Within these ranges, several estimates were derived from relatively high quality data; these articles are highlighted in the review. Prevalence was elevated in subpopulations including emergency responders, refugees, American Indian/Alaska Natives, individuals with heavy substance use, individuals with a past suicide attempt, trans-masculine individuals, and women with prior military sexual trauma. Female sex, lower income, younger age, and behavioral health conditions were identified as risk factors for PTSD. Conclusions: PTSD prevalence estimates varied widely, partly due to different study designs, populations, and methodologies, and recent nationally representative estimates were lacking. Efforts to increase PTSD screening and improve disease awareness may allow for a better detection and management of PTSD.